Infection by the Protozoan Parasite Toxoplasma gondii Inhibits Host MNK1/2-eIF4E Axis to Promote Its Survival - Leroux, Louis-Philippe; Chaparro, Visnu; Jaramillo, Maritza (Frontiers in Cellular and Infection Microbiology, 2020)
The obligate intracellular parasite Toxoplasma gondii reprograms host gene expression through multiple mechanisms that promote infection, including the up-regulation of mTOR-dependent host mRNA translation. In addition to the mTOR-4E-BP1/2 axis, MAPK-interacting kinases 1 and 2 (MNK1/2) control the activity of the mRNA cap-binding protein eIF4E. Herein, we show that T. gondii inhibits the phosphorylation of MNK1/2 and their downstream target eIF4E in murine and human macrophages. Exposure to soluble T. gondii antigens (STAg) failed to fully recapitulate this phenotype indicating the requirement of live infection. Treatment with okadaic acid, a potent phosphatase inhibitor, restored phosphorylation of MNK1/2 and eIF4E regardless of infection. T. gondii replication was higher in macrophages isolated from mice mutated at the residue where eIF4E is phosphorylated (eIF4E S209A knock-in) than in wild-type (WT) control cells despite no differences in infection rates. Similarly, parasitemia in the mesenteric lymph nodes and spleen, as well as brain cyst burden were significantly augmented in infected eIF4E S209A knock-in mice compared to their WT counterparts. Of note, mutant mice were more susceptible to acute toxoplasmosis and displayed exacerbated levels of IFNγ. In all, these data suggest that the MNK1/2-eIF4E axis is required to control T. gondii infection and that its inactivation represents a strategy exploited by the parasite to promote its survival.